The impact of the of Six Sigma to improve the performance of dentists in albaladeat specialized Dental - سعيد سناء عبد الرحيم; جابر زينب جعفر (Journal of Economics and Administrative Sciences, 2020)
The research aims at introducing the principles of six sigma and if it had any effect of the dimensions of six sigma to improve the performance of the dentists and the availability of an appropriate environment in the center Specialist respondent to the application of six sigma principles and how to adopt Specialized Center under the dimensions of the six sigma and if there informed enough with the management methodology six sigma, and if you can adopt six sigma as one of the entrances to reduce medical errors. So Search creating six sigma five dimensions and are (the commitment and support of senior management, the focus on the patient, continuous improvement, training and civil, and infrastructure) as a variable interpretative, and improved performance as a variable-response, so it was determined Specialist Dental Center in Al-baladiat a society for the study, and for the results to be objective and reflect the reality of the quality of medical service and more accurate researcher used random sampling method and distributed a questionnaire research on a sample of 60 dentist, and based on the measurement of research, diagnosis and testing of the link and influence, including relationships variables, research found a set of conclusions recall of which there are difficulties in applying six sigma in practice because of limited financial resources and technological and potential, that the selection of competent people and to improve their abilities and give them adequate opportunity to prove their merit and value their role is a critical factor in the selection of dentists qualified competent, and the need for the administration to provide support and communication with the medical staffs in order to improve their performance so as to contribute to the improvement of the service provided to the patient and that there is a positive and significant correlation between the focus on the patient and improve the performance of dentists in the respondent center which contributes to the provision of health service quality level of the relationship as more focus on providing ways to satisfy the patient’s increased was an indication of the high level of performance. The research came out with a set of recommendations, the most important of which is the rapid response to the requirements of patients, as providing a health service free of defects is the primary goal of the Six Sigma methodology, and through it we achieve the satisfaction of patients with the provided health service and the definition of the importance of improving the performance of medical staff in general and dentists in particular and the continuous quest to spread Six Sigma culture and establishing ethics in support of the outstanding performance of dentists, with a view to identifying ways and methods that develop these skills and help in improving performance in health organizations. Solving the problem (not just fixing) by removing the root cause of that problem, taking advantage of the good talents of dentists and their development and focusing on strengths and realizing that it is not possible to eliminate all aspects of shortcomings and weaknesses only through focusing on improving the performance of workers and addressing weaknesses in performance. Keywords: Six Sigma, performance improvement.